Performance comparison of quantum memories in cesium vapor cells with anti-relaxation coatings - Park, Changhoon; Su, Jing; Hsu, Stanley; Tang, Xiao; Gerrits, Thomas; Slattery, Oliver; Ma, Lijun (Optical Society of America, 2026)
Atomic vapor-cell quantum memories are key devices for quantum information science. Anti-relaxation coatings on the inner surface of the cell suppress ground-state dephasing caused by atom-wall collisions, thereby improving memory performance. Nevertheless, systematic performance comparisons of vapor-cell quantum memories with different anti-relaxation coatings under identical conditions remain limited. Here, we experimentally compare quantum-memory performance in cesium vapor cells with and without anti-relaxation coatings—uncoated, paraffin-coated, and alkene-coated—under otherwise identical conditions to assess coating-dependent effects. Using electromagnetically induced transparency (EIT) as the light storage protocol, we characterize transmission, memory efficiency, and storage lifetime. The alkene-coated cell yields the largest enhancement in retrieval efficiency—more than fourfold relative to the uncoated cell and more than twofold relative to the paraffin-coated cell—while exhibiting a modest (approximately 16%) increase in storage lifetime. These results provide a systematic benchmark for evaluating anti-relaxation coatings and for this instance, identify alkene coatings as an effective choice for improving retrieval efficiency in warm-vapor-cell memories.